1964
DOI: 10.1149/1.2426012
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Reactions of Simple Phenolic Compounds

Abstract: A study of the anodic reactions of phenols was made using the techniques of voltammetry, coulometry, and controlled potential electrolysis. It was shown that two entirely different anodic reactions are possible with phenolic compounds. The first is an electrophilic attack on the aromatic nucleus of the nonionized phenol with the irreversible removal of two electrons to give a mesomeric phenoxonium ion. As an example of this process an electrolysis of 2,6-di-tert-butyl-p-cresol in acetonitrile at a platinum ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

1971
1971
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 22 publications
5
38
1
Order By: Relevance
“…Consequently, a poorly defined film, with continuous structure is formed on the electrode surface. An analogous reaction path was previously proposed for oxidative polymerization of vanillin porphyrins [13], vanillin [14], guaiacol [15], epidotoxin [16] and eugenol [17].…”
Section: Oxidative Electropolymerization Of Curcumin and Ni(ii)curcummentioning
confidence: 68%
See 1 more Smart Citation
“…Consequently, a poorly defined film, with continuous structure is formed on the electrode surface. An analogous reaction path was previously proposed for oxidative polymerization of vanillin porphyrins [13], vanillin [14], guaiacol [15], epidotoxin [16] and eugenol [17].…”
Section: Oxidative Electropolymerization Of Curcumin and Ni(ii)curcummentioning
confidence: 68%
“…Moreover, the procedure for their preparation is usually simple and the properties of the resulting coating can be controlled carefully. Electropolymerization procedure was used successfully for modifying electrode surfaces with Ni(II) cyclam and other similar Ni(II) tetraazamacrocyclic complexes [4] or Ni(II) tetramethyldibezotetraaza (14)anulene [5], and the resulting films showed high catalytic activity toward electrooxidation of alcohols and/or other À OH and À NH 2 containing compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The electrooxidation of vanillin and eugenol on platinum in basic media into the corresponding natural occurring biphenols has been reported. [13,14] Owing to the high costs of platinum, carbon electrode materials are definitely more attractive for technical applications. Unfortunately, the conversion of simple methylated phenols like para-cresol or 2,4-dimethylphenol (1) lead to the formation of the corresponding Pummerers ketone derivative 3 and not to the biphenol.…”
Section: Introductionmentioning
confidence: 99%
“…Vermillion and Pearl [26] have proposed that the first stage of the anodic oxidation of phenol on PbO 2 occurs according to two different mechanisms depending on the pH. They have suggested that, at pH values below the pK a (9.89), the bielectronic discharge of phenol molecules leads to the formation of phenoxonium cations:…”
Section: Introductionmentioning
confidence: 99%